Bulgaria : A Changing Poverty Profile - World Bank (Washington, DC, 2013)
Bulgaria's economic progress in recent years has been notable. Since 1997, the country has implemented a range of structural reforms alongside substantive fiscal and sectoral reforms. Measures have included the introduction of a currency board to stabilize the lev and more aggressive privatization of large state owned enterprises. These developments have led to a significant turnaround from the period of economic crisis in 1996-1997, which was marked by a decline in real Gross Domestic Product (GDP) of 18 percent and annual inflation of 579 percent in 1997. Growth resumed in 1998 and has been sustained. Bulgaria's current government, which took office in July 2001, has affirmed its commitment to the objectives of macrostability, including a continuation of the currency board and market reforms. Poverty in 2001 has become more concentrated among distinct and identifiable groups within the population than in previous years. In this regard, the profile of poverty in Bulgaria has come to resemble poverty patterns in other countries in Central and Eastern European countries more closely. The strong link between unemployment and poverty, and the emergence of children and households in rural areas as high poverty risk groups, as well as ethnic minorities are features of poverty common to ED accession countries. While the concentration of poverty among specific groups indicates that targeting interventions to address poverty in Bulgaria will be easier, on the other hand, these pockets of chronic poverty are more resilient and harder to reach than shallower poverty linked to transient declines in incomes. These developments highlight the need for a long term commitment to poverty reduction in Bulgaria which will require continuity in policy, as well as on-going monitoring and evaluation.